2002
DOI: 10.1021/ol026065j
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Donating Properties of p-Phenylene Phosphine Imides:  An Electrochemical and Spectroscopic Investigation

Abstract: [reaction: see text] Electronic properties of phosphine imide based organic electron donors have been investigated. N,N'-p-Phenylenebis(triphenyl)phosphine imide (Ph(3)P=NC(6)H(4)N=PPh(3), 1) has two reversible single-electron oxidations (0.04 and 0.53 V vs SCE). Spectroscopic investigations of poly(p-phenylene phosphine imide)s (2) are similar to those of polymer model compounds, suggesting formation of localized radical cations on the polymer chains and electronically insulating phosphorus atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Lucht and co-workers have investigated the electron-donating properties of such iminophosphorane moieties in π-conjugated materials in detail to better understand the nature of the PN-bond in these systems as well as the degree of overlap with adjacent π-systems. , Their strong donor character has put the conjugated bis(iminophosphoranes) in the focus of organic electronics, as they might be utilized as efficient hole transport materials. Monomeric ( 252 , 253 ) as well as polymeric materials 254 (Chart ) are accessible by the Staudinger protocol using appropriate diazido precursors and triarylphosphanes, respectively, to afford the materials in good to high yields.…”
Section: π-Conjugated Materials With Phosphorus Multiple Bondsmentioning
confidence: 99%
“…Lucht and co-workers have investigated the electron-donating properties of such iminophosphorane moieties in π-conjugated materials in detail to better understand the nature of the PN-bond in these systems as well as the degree of overlap with adjacent π-systems. , Their strong donor character has put the conjugated bis(iminophosphoranes) in the focus of organic electronics, as they might be utilized as efficient hole transport materials. Monomeric ( 252 , 253 ) as well as polymeric materials 254 (Chart ) are accessible by the Staudinger protocol using appropriate diazido precursors and triarylphosphanes, respectively, to afford the materials in good to high yields.…”
Section: π-Conjugated Materials With Phosphorus Multiple Bondsmentioning
confidence: 99%
“…In other words, intramolecular charge-transfer interactions must be dominant in PFPA-Si. Because of the electron-donating property of phosphoranimine bond, 24 it would facilitate the intramolecular charge-transfer interactions between ferrocene and TCNAQ units in PFPA-Si. Because of the ICT interactions between ferrocene (and/or phosphoranimine) and TCNAQ units, upon scanning anodically, PFPA-Si exhibits three irreversible oxidation waves at the potentials of 0.62, 0.78, and 1.07 V (Figure S29).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The voltammogram of B para , already reported by Escobar et al [3] exhibits two reversible oxidation waves at E 0 = 0.04 and 0.53 V vs. SCE. The EPR spectrum (g = 2.0039) obtained by electrochemical oxidation at a potential slightly superior to the first wave is shown in Fig.…”
Section: Epr Spectramentioning
confidence: 58%
“…The pentavalent phosphorus P@N bonds are robust; they can be incorporated in conjugated polymers and are potentially able to give rise to organic conducting materials [3,4]. As shown by Escobar et al [3], the electron-donating capacity of the iminophosphorane bond is fundamental to explain the properties of these systems; in particular they showed that para bis-iminophosphorane B para possesses two reversible one-electron oxidations. The first chemical oxidation results in a shift of the optical absorption band consistent with the formation of the monocation.…”
Section: Introductionmentioning
confidence: 99%